Genetically engineered eucalyptus expressing pesticidal proteins from Bacillus thuringiensis for insect resistance: a risk assessment evaluation perspective - Avisar, Dror; Manoeli, Alexandre; dos Santos, Anselmo Azevedo; Porto, Antonio Carlos Da Mota; Rocha, Carolina Da Silva; Zauza, Edival; Gonzalez, Esteban R.; Soliman, Everton; Gonsalves, José Mateus Wisniewski; Bombonato, Lorena; Galan, Maria P.; Domingues, Maurício M.; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Eucalyptus covers approximately 7.5 million hectares in Brazil and serves as the primary woody species cultivated for commercial purposes. However, native insects and invasive pests pose a significant threat to eucalyptus trees, resulting in substantial economic losses and reduced forest productivity. One of the primary lepidopteran pests affecting eucalyptus is Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: Geometridae), commonly referred to as the brown looper caterpillar. To address this issue, FuturaGene, the biotech division of Suzano S.A., has developed an insect-resistant (IR) eucalyptus variety, which expresses Cry pesticidal proteins (Cry1Ab, Cry1Bb, and Cry2Aa), derived from Bacillus thuringiensis (Bt). Following extensive safety assessments, including field trials across various biomes in Brazil, the Brazilian National Technical Commission of Biosafety (CTNBio) recently approved the commercialization of IR eucalyptus. The biosafety assessments involved the analysis of molecular genomics, digestibility, thermostability, non-target organism exposure, degradability in the field, and effects on soil microbial communities and arthropod communities. In addition, in silico studies were conducted to evaluate allergenicity and toxicity. Results from both laboratory and field studies indicated that Bt eucalyptus is as safe as the conventional eucalyptus clone for humans, animals, and the environment, ensuring the secure use of this insect-resistant trait in wood production.